PENGUJIAN KOMPOS DAN INOKULAN MIKROBA TERHADAP PERTUMBUHAN TANAMAN SENGON BUTO (Enterolobium cyclocarpum, (WILLD) PADA LAHAN BEKAS TAILING POND DI CIKOTOK - Hartati Imamuddin; Nunik Sulistinah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Soil pollution has been so attracting considerable public attentions over the last decades. Phytoremediation is an emerging technology that uses plants to clean up pollutant soils. The study was carried out in gold mining Cikotok, Banten. Sengon buto (Enterolobium cyclocarpum, (Willd) which is used as cyanogenic plant, compost and microbes inoculant is as stimulator to growth this plant. The experiment consist of K0 as control (plant without compost), K1 as plant + compost and K2 as plant+compost + microbe inoculant, with 3 replicated. The objectives of this experiment were to investigate the potential for phytoremediation of cyanide contaminated soils using hyperaccumulator/cyanogenic plants and to assess the fate and transport of cyanide compounds in soils. The results showed that compost and microbe were able to stimulate growth of Sengon Buto after 7 months planting and to reduce cyanide until 66% Total bacteria in the study was relatively stable but NFB bacteria was decline.